Between Nasab and Heirs: Examining the Status of the Surrogate Mother's Child in Contemporary Islamic Law - Azzahra Hsb, Sakinah; Azizah, Nur (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
The practice of surrogate motherhood raises legal issues in Islam, particularly regarding the validity of lineage and the inheritance rights of the child born. When the pregnancy process involves a woman who is not the legal wife or uses the ovum and uterus of a third party, the lineage becomes unclear and results in the loss of the child's inheritance rights. This study aims to explore the legal status of children born through surrogacy from the perspective of contemporary Islamic jurisprudence, using a normative approach. The research employed a qualitative approach with a legal-normative and theological framework. The findings indicate that Islamic scholars and modern Islamic legal institutions generally reject the legality of this practice as it contradicts the principle of hifz al-nasl. Children born through surrogacy only have a blood relationship with the biological mother who gave birth to them and do not have inheritance rights from the biological father unless there is a valid marriage. In Indonesia itself, there are no specific regulations governing this matter, so legal reforms are needed to address the challenges posed by modern reproductive technologies.